The seed of abundance and misery. Peruvian living standards from the early republican period to the end of the guano era (1820-80) - Twrdek, Linda (2013)
This paper scrutinizes the development of heights in Peru from the early republican period to the end of the guano era (1820-1880). Studying heights of prisoners from the Lima penitentiary, we find that those of prisoners from the lower classes stagnated throughout the period. We argue that the presence of such a valuable export as guano had no positive effects on the standard of living of the middle and lower classes, not even in Lima, where most of the benefits from guano exports were concentrated. After controlling for ethnic and occupational differences throughout the period under consideration, we find no statistically significant regional disparities in living standards. Moreover, we find that ethnic differences were as pronounced during that time as they would have been if no political change had happened, and that they remained unchanged throughout the entire century. In addition, this study is the first to present data on 19th-century Peruvian women.